H₂ and H ͚ satellite attitude controls for combined energy and attitude control systems - Ban, Ying Siang (2015)
Combined Energy Storage and Attitude Control System (CEACS) is a new satellite system developed using flywheels to offer mass reduction, longer operation life and also cost reduction. To date, the demonstration of the CEACS attitude control performance has been limited only to the proportional derivative control (PD) and the active force control-proportional derivative (AFC-PD). Both controllers have their limitations where the PD controller is known to be less sensitive to uncertainties while the AFC-PD requires accurate in-situ measurement, which is not readily available at the moment. This proposed study will focus on improving the performance of small satellites with the CEACS system as the pitch attitude actuator by applying advanced control methods, H2 control and H∞ control. Both controllers were applied on three different classes of satellite, nanosatellite, microsatellite and enhanced microsatellite and simulated via MATLAB™ and SIMULINK® programming for the ideal and non-ideal scenarios. From the testing, it is found that the CEACS pitch attitude performance for both the H2 control and H∞ control can meet the required pitch attitude requirement of 0.2°. The comparison between both controllers shows that the H2 control method has a slightly better pitch attitude performance compared to the H∞ control for ideal and non-ideal scenarios. As for the comparison with the conventional PD controller and the PD-AFC controller, the results indicate that both the H2 and H∞ controllers outperform the conventional PD controller while having a slight advantage over the PD-AFC controller in terms of the attitude performance. However, as the feasibility of the AFC controller is highly dependent on the in-situ measurement of systems where the development of these systems requires time, thus the H2 and H∞ controls are the favourable control options for an immediate deployment of the CEACS system while providing an accurate pitch control in the face of orbit uncertainties.